2008
DOI: 10.1371/journal.pone.0002186
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Epithelial Branching Morphogenesis and Cancer Cell Growth of the Prostate by Wnt Signaling

Abstract: Although Wnt signaling has been shown to be important for embryonic morphogenesis and cancer pathogenesis of several tissues, its role in prostatic development and tumorigenesis is not well understood. Here we show that Wnt signaling regulated prostatic epithelial branching morphogenesis and luminal epithelial cell differentiation in developing rat prostate organ cultures. Specifically, Wnt signaling regulated the proliferation of prostate epithelial progenitor cells. Assessment of the expression levels of a W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 46 publications
8
55
0
1
Order By: Relevance
“…This phenomenon has been reported in the testosterone-treated ORX mouse prostate (Wang et al 2008). Axin mRNA and protein were repressed through 7 days (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…This phenomenon has been reported in the testosterone-treated ORX mouse prostate (Wang et al 2008). Axin mRNA and protein were repressed through 7 days (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…AXIN, which is transcriptionally activated through Wnt signalling [40], directs β-catenin for degradation through ubiquitin-dependent proteolysis and was previously reported to be upregulated in prostate cancer cell lines [41].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Tissues were then sectioned and stained with H&E. Tissues for immunofluorescent staining were fixed in 4% paraformaldehyde/phosphate-buffered saline prior to Declere antigen retrieval (Cell Marque) using a pressure cooker for 10 min and then blocked in 10% donkey serum/ phosphate-buffered saline. Primary antibodies used include rabbit anti-Klf6 (Santa Cruz Biotechnology, Santa Cruz, CA), rabbit anti-Ki67 (LabVision), rabbit anti-␤-galactosidase (1:10,000, MP Biomedical, without antigen retrieval) (19), rabbit anti-androgen receptor (Upstate), rabbit anti-smooth muscle actin (LabVision), rabbit anti-desmin (EuroDiagnostica), rabbit anti-ck14 (Covance), mouse anti-ck8 (Novus), rabbit anti-phospho-Smad1/5/8 (1:500, Cell Signaling), and mouse anti-E-cadherin (BD Pharmingen). Secondary antibodies used to detect respective primary antibodies were anti-rabbit Alexa 488 (Invitrogen) and anti-mouse Alexa 594 (Invitrogen).…”
Section: Generation Genotyping and Reverse Transcription-pcr Of Klf6mentioning
confidence: 99%
“…In addition, the number of main ducts and complexity of ductal branching vary among the three lobes. A number of growth factors/pathways have been implicated in regulating prostatic epithelial proliferation and differentiation, including hedgehog (Hh), 4 bone morphogenic proteins (BMPs), fibroblastic growth factors (FGFs), and Notch and Wnt pathways (12)(13)(14)(15)(16)(17)(18)(19). For example, work done in our laboratory and others showed that sonic hedgehog (Shh) produced in the prostatic epithelium is a negative regulator of prostatic branching morphogenesis, mediated indirectly by periepithelial mesenchymal cells (12)(13)(14)(15).…”
mentioning
confidence: 99%